PERANCANGAN SISTEM INFORMASI AKUNTANSI PEMBELIAN STUDI KASUS : UD XYZ SALATIGA - Purwanto Purwanto (Jurnal Ilmiah SINUS, 2019)
The objective of the company’s business activities is to give gain or profit. One of the ways to meet the objective is by reducing the cost.  The company which does not regulate its purchases will suffer losses. The purpose of the study was to design a purchasing accounting information system to assist in increasing company profits. The research methods were by defining and analyzing system requirements by using Data Flow Diagrams (DFD), Resouces Events Agent (REA), Form Design, Information System Implementation. The result of the study was that the purchasing accounting information system had answered the company's needs in terms of: 1. time effectiveness on recapitulating the purchased order data, 2. Minimizing errors occured in the type and amount of goods to be purchased.